Electrophysiological and MRI evaluation of neurological involvement in Behçet's disease. Issue 6 (June 1989) - Besana, C; Comi, G; Del Maschio, A; Praderio, L; Vergani, A; Medaglini, S; Martinelli, V; Triulzi, F; Locatelli, T
Abstract : Eight patients with stable Behçet's disease were studied by means of multimodality evoked potentials and magnetic resonance imaging to evaluate the possibility of an earlier and objective demonstration of clinical and subclinical Central Nervous System (CNS) involvement. It was shown that both diagnostic techniques are useful for quantitative evaluation of neurological involvement in Behçet's disease; of particular interest was the demonstration of subclinical CNS changes.